2019
DOI: 10.1186/s40814-019-0436-3
|View full text |Cite
|
Sign up to set email alerts
|

Reporting quality of pilot clinical trials in chronic kidney disease patients on hemodialysis: a methodological survey

Abstract: Background The conduct of high-quality pilot studies can help inform the success of larger clinical trials. Guidelines have been recently developed for the reporting of pilot trials. Objective This methodological survey evaluates the completeness of reporting in pilot randomized controlled trials in chronic kidney disease patients on hemodialysis (HD patients) and explores factors associated with better completion of reporting. Methods The au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Third, the bar to demonstrate feasibility may be artificially low if studies are not identifying and addressing the specific challenges in the clinical field of interest. This may be accentuated if feasibility studies rely on a formulaic design [ 8 ]. Fourth, the team may be reluctant to publish the conclusion that a trial is not feasible.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Third, the bar to demonstrate feasibility may be artificially low if studies are not identifying and addressing the specific challenges in the clinical field of interest. This may be accentuated if feasibility studies rely on a formulaic design [ 8 ]. Fourth, the team may be reluctant to publish the conclusion that a trial is not feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the view that feasibility studies are essential before conducting a RCT is leading to the design of studies which are likely to ‘succeed’ and therefore lack equipoise or do not focus on the most important uncertainties which need to be addressed in relation to the specific trial. As shown by the existing literature, it is often the case that feasibility studies in certain topic areas do not maximise their potential benefit and focus on the key uncertainties [ 8 , 11 ] and instead adopt a generic design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pilot and feasibility randomised trials in surgery will be poorly reported as per the CONSORT extension for pilot trials. We predict that the majority of included studies will report less than half of the items included in the CONSORT extension to randomised pilot and feasibility trials (ie, >50% of pilot randomised controlled trials (RCTs) will report <50% of the CONSORT items) 19 20 24…”
Section: Methodsmentioning
confidence: 99%
“…It is a 40-item checklist that applies to any randomised trial in which a future definitive randomised trial, or some component of it, is scaled down to assess the feasibility of the future randomised trial, regardless of the design (eg, factorial and cluster) 17. Previous methodological reviews have evaluated pilot randomised trials as per the CONSORT extension to randomised pilot and feasibility trials in chronic kidney disease and psychiatric illness; however, a review of this nature has yet to be conducted with surgical pilot randomised trials 19 20. Two additional important concepts of reporting quality include spin reporting and consistency between abstract and full-text reporting.…”
Section: Introductionmentioning
confidence: 99%